Evolution of microstructure, texture and residual stress of AZ31 Mg alloy in hot extrusion process. (15th June 2021) - Kang, Lei; Liu, Weirong; Zhang, Xiongbo; Chen, Leng
Abstract: In this work, we have investigated the microstructure, texture, and residual stress of AZ31 Mg alloy at several higher extrusion temperatures (360 °C, 380 °C, 400 °C) and speeds (1 m min −1, 2 m min −1, 3 m min −1 ). Results show that the bimodal microstructure can be observed in all extruded Mg alloys, consisting of the fine grains in dynamic recrystallization (DRX) zone and the coarse grains in non-dynamic recrystallization (non-DRX) zone. The non-monotonic relation between average grain diameter and extrusion speed has been found. It is attributed to the promoted nucleation and inhibited grain growth at higher extrusion speed. The bimodal microstructure can maintain the stability of sharp 0002 basal texture. Schmid Factor (SF) is calculated to explain the mechanism of basal texture formation. By employing XRD with cos α method, the residual stress has been measured. The major origin of residual stress release at higher extrusion temperature is the grain growth, rather than the strengthening of basal texture. The anisotropy of residual stress distribution is related to the coupling effect of grain growth and evolution of basal texture of extruded Mg alloys.